ZNANSTVENO ISTRAŽIVAČKI PROJEKT" Povezanost kvalitete života i psihološkog aspekta bolesnika s acne vulgaris" - Šitum, Mirna (Array, 2003)
Self assessment of acne severity is often more severe than dermatological clinical evaluation what is very important fact in understanding the necessity of individual approachment to the patient. Isotretinoin is the drug which is indicated in the treatment of severe form of the disease, but in last period its application is suggested in moderate form of acne with prominent cicatricial liability or when the disease has strong psychological impact on patients life. Last 15 years some data of possible association with depression and suicidal tendency during treatment with isotretinoin appeared. In our Clinic a prospective clinical trial is in course in which standardised psychometric questionnaires (APSEA, DSQL, BDI, STAI, MPS) and psychological interview are used in order to evaluate psychological status of patients and the influence of isotretinoin on psychological status of patients during treatment of acne vulgaris.